Pengembangan Jiwa Entrepreneur Santri Di Pondok Pesantren Mu’inul Islam - Dina Amaliah Maulida; Candra Eka Jaya; Ichsan Iqbal (Jurnal Ekonomi dan Bisnis Digital, 2024)
Entrepreneurship education is an effort to build and develop an entrepreneurial spirit. Efforts to improve the quality of human resources in Islamic boarding schools must be carried out in accordance with the vision, mission, culture and identity of Islamic boarding schools as institutions for education, da'wah and empowerment of the people based on the Al-Quran and Hadith. Growing and forming an interest in entrepreneurship in students at Islamic boarding schools requires motivation and recognition of one's potential. This research aims to try to develop the spirit of students to manage the results of the facilities and infrastructure provided by the boarding school. Type and Approach This research is field research using a qualitative approach. The results of the research show that basically the students at the Mu'inul Islam Islamic Boarding School are indeed educated and directed to learn entrepreneurship. This is of course supported by the facilities owned by the Islamic boarding school. Santri have a better business spirit, but they don't really understand the concept of selling online and putting logos on processed products.